From few-cycle femtosecond pulse to single attosecond pulse-controlling and tracking electron dynamics with attosecond precision - Wang, He (Kansas State University, 2010)
The few-cycle femtosecond laser pulse has proved itself to be a powerful tool for controlling the electron dynamics inside atoms and molecules. By applying such few-cycle pulses as a driving field, single isolated attosecond pulses can be produced through the high-order harmonic generation process, which provide a novel tool for capturing the real time electron motion. The first part of the thesis is devoted to the state of the art few-cycle near infrared (NIR) laser pulse development, which includes absolute phase control (carrier-envelope phase stabilization), amplitude control (power stabilization), and relative phase control (pulse compression and shaping). Then the double optical gating (DOG) method for generating single attosecond pulses and the attosecond streaking experiment for characterizing such pulses are presented. Various experimental limitations in the attosecond streaking measurement are illustrated through simulation. Finally by using the single attosecond pulses generated by DOG, an attosecond transient absorption experiment is performed to study the autoionization process of argon. When the delay between a few-cycle NIR pulse and a single attosecond XUV pulse is scanned, the Fano resonance shapes of the argon autoionizing states are modified by the NIR pulse, which shows the direct observation and control of electron-electron correlation in the temporal domain.
Keywords: attosecond dynamics; few-cycle femtosecond; pulse shaper; argon autoionization; single attosecond pulse; Physics, Atomic (0748); Physics, Optics (0752)